Democracia constitucional liberal em crise: o custo de se tolerar o intolerável - Pinheiro, Igor Vieira (2025)
This research aimed to analyze the cost of tolerating authoritarian leaders and movements within a liberal constitutional democracy. It is important to highlight that one of the most obvious costs is the gradual erosion of democratic institutions. Authoritarian leaders often try to weaken the judiciary, control the media and manipulate electoral processes to consolidate their power. In addition, tolerance of hate speech and divisive rhetoric can polarize society, creating an "us versus them" environment that hinders dialogue and cooperation. Therefore, the aim was to characterize the essence of this democracy, as well as to demonstrate the crises that they are facing and to raise doubts about absolute tolerance, the primacy of pluralism and their contribution to the process of democratic erosion. In this sense, this research sought to define which type of democracy is dying (or going through crises), focusing specifically on liberal constitutional democracy; to carry out a careful analysis of the democratic crises observed globally and the rise of political outsiders of a populist and authoritarian nature; as well as tolerance in liberal constitutional democracies, highlighting the delicate balance they must maintain between promoting pluralism and protecting against intolerant movements